SYNTHESIS OF 5, 7-DIHYDROXy-8-C-PRENYLFLAVANONE (Biological Sciences - PJSIR, 2001)
5,7-Dihydroxy-8-C-prenyltlavanone (VII, glabranin) Mitscher et a11983) isolated from the roots and stems of Glycyrrizalepidota has been synthesized by following unambigous route. All the new products have been characterized on thebasis of spectral data.